Chemical Composition and Antioxidant Potential of Aristolochia maurorum Above-groud Extract: Phenolic and Phytochemical Analysis - TORUNOGLU, Emine İncilay and AYTAR, Erdi Can and DURMAZ , Alper and AYDIN, Betül and ÇOLAK, Ayşe Melda (ISPEC Tarım Bilimleri Dergisi, 2024)
The aim of this study is to evaluate the antioxidant activity, chemical composition, phenolic components, and fatty acid content of extracts obtained from the aerial parts of Aristolochia maurorum. The above-groud of A. maurorum were collected from remote areas in Havza and Kavak districts of Samsun province, Turkey. The plants were dried, powdered, and extracted with methanol. The total phenolic contents, total flavonoid contents, total tannin contents, and total proanthocyanidin contents of the extracts were determined using spectrophotometric methods. Additionally, DPPH free radical scavenging activity was measured. The fatty acid contents were analyzed using gas chromatography-mass spectrometry (GC-MS). The methanol extract of A. maurorum above-groud contains high levels of phenolic compounds and exhibits strong antioxidant activity. The total phenolic content of the extract was found to be 12.24 ± 0.91 mg GAE/g, total flavonoid content 27.45 ± 0.31 mg QE/g, total tannin content 28.41 ± 0.31 mg GAE/g, and total proanthocyanidin content 155.24 ± 32.20 mg CAE/g. The DPPH free radical scavenging activity showed an IC50 value of 506.29 ± 38.35 mg/mL. GC-MS analyses demonstrated that the extract contains various bioactive compounds, notably eicosane, which is reported to have anti-inflammatory, analgesic, and antipyretic properties. In conclusion, extracts derived from the above-groud of A. maurorum are rich in phenolic compounds and exhibit high antioxidant activity. These findings may contribute to a better understanding of the potential therapeutic uses of A. maurorum and could aid in the development of future plant-based medicines.